Implementasi Aplikasi Mobile Augmented Reality Untuk Pengenalan Sejarah Ikon Kota Di Indonesia - Ibnu Risky Pramudito; Ikrimach (The Indonesian Journal of Computer Science, 2023)
This research is the result of observations made by researchers about the lack of interesting and educational learning media to introduce the history of city icons in Indonesia. Along with the times, there are many learning methods that utilize technological advances in their application. One technology that can be applied is Augmented Reality technology. Augmented Reality is a technology that unites two-dimensional or three-dimensional virtual objects into a real environment and then projects them in Real Time. This research uses a data collection process by conducting a literature study, namely collecting relevant information from thesis sources, scientific journals, and the internet. The results of this study are expected to add insight into the history of city icons in Indonesia and can add to the user experience about Augmented Reality technology.